Seismic Evaluation of Reinforced Concrete Buildings - Singh, Taranpreet (My University, 2007)
The Buildings, which appeared to be strong enough, may crumble like houses of cards during earthquake and deficiencies may be exposed. Experience gain from the recent earthquake of Bhuj, 2001 demonstrates that the most of buildings collapsed were found deficient to meet out the requirements of the present day codes. Due to wrong construction practices and ignorance for earthquake resistant design of buildings in our country, most of the existing buildings are vulnerable to future earthquakes. In light of these facts, it is imperative to seismically evaluate the existing building with the present day knowledge to avoid the major destruction in the future earthquakes. The Buildings found to be seismically deficient should be retrofitted/strengthened. The present study deals with the evaluation of R.C buildings using inelastic method (Pushover Analysis). Capacity Curve, which is Load-Deformation Plot is the Output of Pushover Analysis. As, Pushover Analysis is Non-Linear Static Analysis, so the Load-Deformation Curve can be obtained from ANSYS. Finite Element Software ANSYS 5.4 is used to perform the Non-Linear Static Pushover Analysis and Cracking pattern can also be observed in ANSYS. Cracking Pattern provides the need for Strengthening required for particular Elements. Firstly, a symmetrical building is analysed using ANSYS for the procedure development as per ATC-40. Then, Seismic Evaluation is performed on unsymmetrical building (L-shape), which is designed in the first part as without considering seismic effect and in the second part, Analysis is carried out on the same building designed seismically as per I.S 1893:2002. The results have been compared for these two Analysis cases and Strengthening is suggested for the affected members.
Keywords: Seismic Evaluation; Reinforced Concrete; Load-Deformation Curve; Capacity Spectrum